Lithium Storage: 3D Selenium Sulfide@Carbon Nanotube Array as Long‐Life and High‐Rate Cathode Material for Lithium Storage (Adv. Funct. Mater. 43/2018). (22nd October 2018) - Fan, Hai‐Ning; Chen, Shan‐Liang; Chen, Xiao‐Hua; Tang, Qun‐Li; Hu, Ai‐Ping; Luo, Wen‐Bin; Liu, Hua‐Kun; Dou, Shi‐Xue
Abstract : Encapsulating Se x S8− x into vertically‐aligned carbon nanotubes co‐doped with boron and nitrogen, yields a three‐dimensional selenium sulfide@carbon nanotube array. As Xiao‐Hua Chen, Wen‐Bin Luo, and co‐workers describe in article number1805018, such arrays enable fast migration to realize excellent rate capability and efficient utilization of the Se x S8− x loaded inside. Volumetric expansion and the polysulfide shuttling phenomenon during the cycling process are reduced, enabling excellent lithium storage capability.